2018
DOI: 10.1186/s12887-018-1168-x
|View full text |Cite
|
Sign up to set email alerts
|

End-of-life decisions and practices for very preterm infants in the Wallonia-Brussels Federation of Belgium

Abstract: BackgroundVery preterm birth (24 to < 32 week’s gestation) is a major public health issue due to its prevalence, the clinical and ethical questions it raises and the associated costs. It raises two major clinical and ethical dilemma: (i) during the perinatal period, whether or not to actively manage a baby born very prematurely and (ii) during the postnatal period, whether or not to continue a curative treatment plan initiated at birth. The Wallonia-Brussels Federation in Belgium counts 11 neonatal intensive c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 24 publications
0
24
0
1
Order By: Relevance
“…On the contrary, a subset of HCPs even thought there were guidelines available when in fact there were not. Aujoulat et al ( 67 ) similarly showed a subgroup of HCPs who were not aware of the protocols or standardized procedures regarding PnPC. This means that despite the implementation of a guideline, continued information and further training in PnPC within centers remains essential.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, a subset of HCPs even thought there were guidelines available when in fact there were not. Aujoulat et al ( 67 ) similarly showed a subgroup of HCPs who were not aware of the protocols or standardized procedures regarding PnPC. This means that despite the implementation of a guideline, continued information and further training in PnPC within centers remains essential.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, another representative study of those 11 French-speaking neonatal intensive care units, which had a very high response rate, was not taken into account. 2…”
Section: Dear Editormentioning
confidence: 99%
“…We would like to point out that the authors wrongly described the study as a nationwide survey as it did not include the 11 centres in the French‐speaking part of the country. Furthermore, another representative study of those 11 French‐speaking neonatal intensive care units, which had a very high response rate, was not taken into account . This earlier study led to quite different results and conclusions, which could have broadened the discussion and revealed the subtle differences in the ethical and legal implications of the subject, as well as the conclusions drawn by Dombrecht et al…”
mentioning
confidence: 99%
“…One of these problems is related to the provision of advanced care for neonates with poor prognoses ( 1 ). Accordingly, one of these advanced care modalities is end-of-life care provided for terminally ill neonates ( 2 ). This type of care is considered standard practice in NICUs ( 3 ).…”
Section: Introductionmentioning
confidence: 99%